A Novel Dominant Mutation in Plakoglobin Causes Arrhythmogenic Right Ventricular Cardiomyopathy - Asimaki, Angeliki (American Society of Human Genetics, 2007)
Arrhythmogenic right ventricular cardiomyopathy (ARVC) is an inherited disorder associated with arrhythmias and sudden death. A recessive mutation in the gene encoding plakoglobin has been shown to cause Naxos disease, a cardiocutaneous syndrome characterized by ARVC and abnormalities of hair and skin. Here, we report, for the first time, a dominant mutation in the gene encoding plakoglobin in a German family with ARVC but no cutaneous abnormalities. The mutation (S39_K40insS) is predicted to insert an extra serine residue at position 39 in the N-terminus of plakoglobin. Analysis of a biopsy sample of the right ventricle from the proband showed markedly decreased localization of plakoglobin, desmoplakin, and connexin43 at intercalated discs in cardiac myocytes. A yeast-two-hybrid screen revealed that the mutant protein established novel interactions with histidine-rich calcium-binding protein and TGFβ induced apoptosis protein 2. Immunoblotting and confocal microscopy in human embryonic kidney 293 (HEK293) cell lines transfected to stably express either wild-type or mutant plakoglobin protein showed that the mutant protein was apparently ubiquitylated and was preferentially located in the cytoplasm, suggesting that the S39_K40insS mutation may increase plakoglobin turnover via proteasomal degradation. HEK293 cells expressing mutant plakoglobin also showed higher rates of proliferation and lower rates of apoptosis than did cells expressing the wild-type protein. Electron microscopy showed smaller and fewer desmosomes in cells expressing mutant plakoglobin. Taken together, these observations suggest that the S39_K40insS mutation affects the structure and distribution of mechanical and electrical cell junctions and could interfere with regulatory mechanisms mediated by Wnt-signaling pathways. These results implicate novel molecular mechanisms in the pathogenesis of ARVC.